Penyuluhan Gizi Seimbang Dalam Upaya Pencegahan Anemia dan Gizi Kurang Pada Santri/Santriwati Pondok Pesantren Wihdatul Ulum YW-UMI: Balanced Nutrition Counseling to Prevent Anemia and Malnutrition in Santri / Nuns of Wihdatul Ulum YW-UMI Islamic Boarding School - Yusuf, Rezky Aulia; Agus, Al-Ikhsan; Sultan, Sulfitra; Pada, Andi Tenri; Adelia, Intan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The eating habits of adolescents in Indonesia, such as eating triple-carbo (noodles, rice, fried foods), hobbies of consuming sweet drinks, consuming less vegetables and fruit, and being lazy to exercise, are the causes of high cases of anemia, obesity, and malnutrition in adolescents. Lack of knowledge related to healthy eating patterns or balanced nutrition is the cause. Therefore, the form of health promotion carried out in this service is counseling using interactive lecture and discussion methods. The lecture/counseling is done within 2 hours. The counseling participants were 32 grade 11 students and female students at the Wihdatul Ulum YW-UMI Islamic boarding school in Kab. Gowa. The data was obtained from the pre-test which was conducted, and it was found that there were only 5-7 santri (15.6%-21.9%) female students who knew about anemia and the concept of balanced nutrition. After conducting counseling on the post-test, it was obtained 22-29 (68.8%-90.6%) of the counseling participants had knowledge related to anemia and balanced nutrition. It can be concluded that it is important to carry out counseling on balanced nutrition and anemia on an ongoing basis, in an effort to improve adolescent behavior in preventing anemia and malnutrition through increased knowledge.